Cosmetic colouring by Bearded Vultures Gypaetus barbatus: still no evidence for an antibacterial function - Margalida Vaca, Antoni; Braun, Markus S.; Wink, Michael (PeerJ, 2019)
Bearded Vultures regularly visit ferruginous springs for cosmetic purposes to obtain their reddish plumage colouration. Different hypotheses have been proposed to explain this deliberate application of adventitious colouration: (1) to signal individual dominance status; (2) to exploit an anti-bacterial effect of iron oxides or ochre to reduce feather degradation by bacteria and, in parallel (3) to enable incubating birds to transfer this protection to their developing embryos to increase hatching success. Here, we re-evaluate the antibacterial hypothesis using three experimental approaches: (a) by applying feather-degrading bacteria to stained and unstained bearded vulture feathers; (b) by assessing the antibacterial activity of ochre; and (c) by comparing the breeding success of orange individuals with pale ones. Our findings suggest that the in vitro addition of feather degrading Bacillus licheniformis to naturally stained Bearded Vulture feathers did not retard feather degradation compared to controls. Iron particles from red soil (ochre) or iron salts had no antibacterial effect on the growth of three species of bacteria (Escherichia coli, Kocuria rhizophila and Bacillus licheniformis), incubated either in the dark or under visible light. Finally, breeding success did not differ between territories occupied by pale individuals versus orange ones. These results run counter to the hypothesis that iron oxides have an antibacterial role in Bearded Vultures. The use of red soils by Bearded Vultures may function as a territorial status signal, but may also be involved in other processes, such as pair formation and the long-term maintenance of the pair bond, as suggested for the closely related Egyptian vulture Neophron percnopterus.
Gesehen am 28.06.2019